2017
DOI: 10.1177/0308518x17715638
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of higher education on the intergenerational transmission of residing in poverty neighbourhoods

Abstract: It is well-known that socioeconomic outcomes and (dis)advantage over the life course can be transmitted from parent to child. It is increasingly suggested that these intergenerational effects also have a spatial dimension, although empirical research into this topic remains scarce. Previous research from Sweden and the United States shows that children who grow up in disadvantaged neighbourhoods experience long-term exposure to such neighbourhoods in their adult lives. This study contributes to the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(88 citation statements)
references
References 48 publications
2
81
1
Order By: Relevance
“…Turning to the European experience, van Ham et al (2014) demonstrated that, even in a strong welfare state country such as Sweden, where inequalities are substantially lower than in the United States, similar intergenerational transmissions of place still occurred (see also Gustafson, Katz, and € Osterberg 2016). Recently, de Vuijst, van Ham, and Kleinhans (2017) demonstrated similar findings using population register data from The Netherlands. Taken together, these findings suggest that to understand adult spatial outcomes in the neighborhood hierarchy-in other words, who lives in which types of neighborhoodswe must take into account childhood neighborhood experiences as well as other parental resources.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Turning to the European experience, van Ham et al (2014) demonstrated that, even in a strong welfare state country such as Sweden, where inequalities are substantially lower than in the United States, similar intergenerational transmissions of place still occurred (see also Gustafson, Katz, and € Osterberg 2016). Recently, de Vuijst, van Ham, and Kleinhans (2017) demonstrated similar findings using population register data from The Netherlands. Taken together, these findings suggest that to understand adult spatial outcomes in the neighborhood hierarchy-in other words, who lives in which types of neighborhoodswe must take into account childhood neighborhood experiences as well as other parental resources.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In addition, newcomers are more likely to live where existing communities are already established. These intergenerational neighbourhood patterns are still shown to be much stronger for ethnic minorities than for other groups (van Ham et al, 2014;de Vuijst, van Ham and Kleinhans, 2015). Neighbourhood effects include socialisation processes (e.g.…”
Section: Migrants' Concentration In Certain Neighbourhoods Is Visiblementioning
confidence: 99%
“…For example, the concentration of poverty of the neighbourhood where parents live influences (or is related to) the concentration of poverty of their children's school, and this will affect the outcomes of these children later in life (through contextual school and neighbourhood effects). There is strong intergenerational transmission of poverty and living in poverty neighbourhoods from parents to children, and these children affect their own children as they grow up (Van Ham et al, 2014;De Vuijst et al, 2017;Hedman et al, 2017). These individual outcomes, in turn, reinforce the sorting of different socio-economic groups into different neighbourhoods.…”
Section: Introductionmentioning
confidence: 99%